Bioaccessibility of iron, zinc, and copper from edible insects available on the European market - M.A.J. Lopes da Costa; A. Angaïts; K. Bierła; J.S. de Gois; J. Szpunar (Applied Food Research)
Consumption of insects contributes increasingly to sustainable nutrition in the context of global food security. This study investigates the total content and bioaccessibility of essential trace elements Fe, Zn, and Cu in various edible insects. Samples of, among others, mealworms (Tenebrio molitor), silkworms (Bombyx mori), sago worms (Rhynchophorus ferrugineus), crickets (Gryllus bimaculatus), black scorpions (Heterometrus longimanus), and weaver ants (Oecophylla smaragdina) were analysed. Inductively coupled plasma mass spectrometry (ICP-MS) determined significant variability in metal content among different insect species, with an overall content higher than in meat. Bioaccessibility studies were conducted using pepsin, pancreatin and bile salts, to simulate gastrointestinal digestion conditions, as is standard in such studies. The bioaccessibility of Fe, Zn, and Cu ranged from 45 % to 65 % and was generally higher in mealworms than in Orthoptera species. Size exclusion chromatography (SEC-ICP-MS) provided insight into the molecular forms of Fe, Zn, and Cu during gastric and intestinal digestion. Intense peaks in the elution range of low molecular mass compounds were observed in the intestinal digests, suggesting complexation of the metal ions with organic ligands. The study highlights the nutritional potential of edible insects as a rich source of essential elements, such as Fe, Zn, and Cu.